Призрачный курган скифского времени у города Сумы - Логинова, Е.Ю. (Археологія і давня історія України, 2018)
В 1926 г. в Государственный Эрмитаж со склада древностей ГАИМК была передана коллекция
предметов, якобы происходящих из кургана у г. Сумы Харьковской губ. Судя по записи в инвентарной
книге музея, производством этих раскопок занимался Н. Е. Макаренко в 1915 г. Однако никаких
документов, подтверждающих эти исследования, найти не удалось. Особый интерес в эрмитажной коллекции представляют многочисленные железные детали от двух повозок скифского типа. Автор рассматривает альтернативную версию происхождения вещей. In 1926 collection of items that allegedly were founded
in a mound near the Sumy city of Kharkov province was
transferred to the State Hermitage museum from the storehouse
of antiquities of the State Academy for the History of Material Culture. According to the information given in
the museums inventory book, this mound was excavated by N. E. Makarenko in 1915. However we couldn’t find any
documents confirming this research. Even if the mound near the Sumy city existed, details of its structure as well
as circumstances of the items discovery are still unknown. The most of peculiar interest items in the Hermitage collection
are numerous iron parts of two Scythian-type wagons. In this article we have proposed the reconstruction of
the wheels of these wagons that based in the analysis of the items. For some parts of wagons we have found analogies
in the Scythian mounds in the Dnieper and the Kuban areas. At the same time, in the Hermitage collection there
are Sindo-Meotian type swords and Meotian pottery of the IV century BC. Considering this fact, we have reviewed an
alternative version of the origin of wagons parts. Some indirect signs allow us to correlate items from a mound near
the Sumy city with the famous Elizabethan burial mounds. This fact is confirmed also by the comparison items from
Hermitage collection with archive documents of excavations of the Elizabethan burial ground, in particular, with
the photo of the wheels that were founded in the mound, excavated in 1915.